Effects of Alchemilla vulgaris on growth performance, carcass characteristics and some biochemical parameters of heat stressed broilers - KÖSEMAN, A.; AKDEMIR, F.; ÜREMIŞ, N.; ŞEKER, I.; TÜRKÖZ, Y. (Journal of the Hellenic Veterinary Medical Society, 2021)
This study aimed to investigate the effects of Alchemilla vulgaris (A. vulgaris) on growth performance, carcass characteristics, and biochemical parameters in broilers exposed to high environmental temperature conditions. A total of 45 broilers of 21 days of age (Ross 308) were used and grouped as the control group (C), and the groups with the addition of 1% (G1), or 3% (G2) A. vulgaris to chicken diet, respectively. In this study, the body weights of heat stressed broilers were significantly different on the 35th day and onwards. Feed intake was higher in the control group. Feed conversion ratio (FCR) was better in groups G1 and G2 compared to control on the 36th and 42nd day, the FCR was better on the 21st- 42nd days. The highest hot and cold carcass performance were observed in group G2 (79.72±0.93% and 78.02±0.99, respectively), and the lowest values were observed in group C (76.26±1.13% and 75.70±1.20%, respectively). A. vulgaris, reduced serum malondialdehyde (MDA) levels as numerically, and suppressed lipid peroxidation in a dose-dependent manner. It had significant effects on monocytes (MON %, MON count), platelets (PLT), and plateletcrit (PCT) parameters only. In conclusion, the deleterious effects of high environmental temperature in broilers could be partially reversed by A. vulgaris addition to the diets between days 21 and 42.